2020
DOI: 10.3390/en13040819
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Type of Fertilization and the Addition of Glycerol on the Quality of Spring Rape Straw Pellets

Abstract: This paper presents an analysis of selected qualitative characteristics of pellets produced from rape straw obtained from cultivations subjected to different fertilization treatments and from mixtures of straw selected for testing with crude glycerol obtained as a by-product from biodiesel production. The assessment focused on the following qualities of the obtained pellets: Moisture content, mechanical durability, heating value and main elements, that is, carbon, hydrogen, nitrogen, sulphur, chlorine and oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Mechanical durability is a crucial parameter concerning transport and logistics. Many standards refer to this quantity [52]. In general, as described in methods, we required about 500 g of pellets per test.…”
Section: Laboratory-scale Analysismentioning
confidence: 99%
“…Mechanical durability is a crucial parameter concerning transport and logistics. Many standards refer to this quantity [52]. In general, as described in methods, we required about 500 g of pellets per test.…”
Section: Laboratory-scale Analysismentioning
confidence: 99%
“…Zang and others [43] believe that the addition of glycerin waste to solid fuels could have a beneficial effect on reducing NO x emissions as well as the formation of smaller amounts of ash. It was also observed that the addition of waste glycerol to biomass pellets reduces the bulk density and ash content and simultaneously increases the calorific value [44][45][46][47][48]. In turn, Potip et al [49] attempted to co-incinerate waste glycerol with ground coffee and showed that with the increase in the addition of glycerin waste, the temperature and combustion rate increase, without affecting the exceedance of standards for exhaust gases such as CO, NO 2 or SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This also led to an increase in the rate of high-temperature corrosion [ 22 ]. For this reason, monitoring the content of such elements is important in fuels intended for energy production [ 23 ].…”
Section: Introductionmentioning
confidence: 99%